PENGARUH NEGARA ASAL DESAIN DAN NEGARA ASAL PEMBUATAN PRODUK PADA KUALITAS YANG DIPERSEPSIKAN DENGAN KETERLIBATAN SEBAGAI PEMODERASI : SEBUAH STUDI EKSPERIMEN - , Rindang Matoati, SE., Dr. Ir. Suci Paramitasari Syahlani ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study examines the effect of country of design and country of manufacturingâs product on perceived quality with involvement as moderating variable. The laboratory experiments were conducted with a 2x2x2 factorial design. This study used undergraduate students from universities in Daerah Istimewa Yogyakarta. The data was analyzed with ANOVA. The results showed there was no difference between high and low country of design on perceived quality, there is significantly difference between high and low country of manufacturingâs product on perceived quality, the higher country of design increased perceived quality, and involvement as moderating variable only affected on the relationship between country of design and perceived quality.